2016
DOI: 10.1038/srep33698
|View full text |Cite
|
Sign up to set email alerts
|

TRIM52 inhibits Japanese Encephalitis Virus replication by degrading the viral NS2A

Abstract: The members of tripartite-motif containing (TRIM) protein participate in various cellular processes and play an important role in host antiviral function. TRIM proteins exert their antiviral activity either directly by degrading viral proteins through their E3 ligase activity, or indirectly by promoting host innate immunity. This study demonstrated for the first time that TRIM52 is a novel antiviral TRIM protein against Japanese encephalitis virus (JEV) infection. Overexpression of TRIM52 restricted JEV replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…A recent study showed that the E3-ubiquitin ligase TRIM52, which belongs to the TRIM family of proteins, regulates JEV infection by directly interacting with NS2A of JEV and leading to NS2A degradation40. Whether Nedd4 can directly interact with JEV nonstructural proteins to affect autophagy activity and virus infection, and if these molecules and pathways are also exploited for replication by the emerging infectious neurotropic Flaviviruses , such as Zika virus and West Nile virus (WNV), remain interesting avenues to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the E3-ubiquitin ligase TRIM52, which belongs to the TRIM family of proteins, regulates JEV infection by directly interacting with NS2A of JEV and leading to NS2A degradation40. Whether Nedd4 can directly interact with JEV nonstructural proteins to affect autophagy activity and virus infection, and if these molecules and pathways are also exploited for replication by the emerging infectious neurotropic Flaviviruses , such as Zika virus and West Nile virus (WNV), remain interesting avenues to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Song, et al Veterinary Microbiology 239 (2019) 108498 budding and release of influenza virus . TRIM family proteins also interfere at multiple stages of the viral life cycle, including degrading viral proteins (Fan et al, 2016), decreasing gene expression and impeding viral assembly (Barr et al, 2008;Wu et al, 2006); however, as an immunosuppressive virus, PRRSV can negatively regulate the host immune response to promote viral propagation via several pathways, including multiple interferon-pathway suppression (Kim et al, 2010;Beura et al, 2010;Li et al, 2010), host antiviral protein degradation (Huang et al, 2016(Huang et al, , 2014, disturbance of monocyte/ macrophages, B cell, and T cell development (Huang et al, 2015;Loving et al, 2015;Fan et al, 2015), and reduced expression of antigen presenting molecules (Chen et al, 2018). In the present study, we found that HP-PRRSV infection promoted S100A9 expression in both PAMs and Marc-145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…JEV infects a variety of cell types from diverse species (including mammals, birds, amphibians, and insects), suggesting that JEV can likely access multiple cell types using multiple host receptors 14 . In recent years, tremendous progress has been made in understanding the viral components required for the various steps of JEV entry and replication, but little is known about the host cell components involved in this process [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%